Challenges and solutions in remote laboratories. Application to a remote laboratory of an electro-pneumatic classification cell. (July 2015) - Prada, Miguel A.; Fuertes, Juan J.; Alonso, Serafín; García, Sergio; Domínguez, Manuel
Abstract: The field of remote laboratories has been developed over the years. These laboratories are valuable educational tools that allow students and faculty interact with real equipment through the Internet, as if they were physically in front of the system. When a remote laboratory is developed, many technical difficulties are found, mainly with respect to the links between the different elements such as physical system, database and clients. In this work, we analyze the challenges and propose approaches to develop remote laboratories that achieve flexibility, scalability and greater educational value. In particular, we present a remote laboratory for automatic control, which includes an electro-pneumatic classification cell. The architecture of the laboratory is based on the three-tier architecture (physical system layer, server layer and client layer). The client layer has been implemented with web standards such as HTML5, AJAX and CSS3, the clients interact with the system using a content management system and the communication interface between the physical system and the database uses a middleware based on OPC (Ole for Process Control). Engineering students have regularly used the remote laboratory and they have evaluated it through surveys. Highlights: We review the main challenges of remote laboratories and propose solutions. We present a middleware based on OPC for the communication with the physical systems. We present client rich applications based on JavaScript and HTML5. We test the technological platform with the addition of an electro-pneumatic classification cell. We propose practical tasks and evaluate their educational value through feedback from students.